Non-fragile robust H[infinity] control for uncertain spacecraft rendezvous system with pole and input constraints - Gao, X.; Teo, Kok Lay; Duan, G. (Taylor & Francis, 2012)
This article investigates the robust H1 control problem for a class of spacecraft rendezvous systems with parameter uncertainties and subject to input constraint, pole constraint and external and controllerperturbations. Based on the Lyapunov theory, a sufficient condition for the existence of the non-fragile robust state-feedback controller is given in terms of linear matrix inequalities (LMIs). Then, proper non-fragile controller design can be cast as a convex optimisation problem subject to LMI constraints. With the obtained controller, the spacecraft rendezvous mission can be accomplished. An illustrative example is provided to show the effectiveness of the proposed control design method.